Inquiry-based learning as a facilitator to student engagement in undergraduate and graduate social work programs - Archer-Kuhn, Beth; Lee, Yeonjung; Finnessey, Savannah; Liu, Jacky (Teaching and Learning Inquiry, 2020)
This seven-cohort mixed methods study examines student engagement in their learning in higher education utilizing inquiry-based learning. The study was conducted in varied settings (on-campus, in community, and study abroad), and across various degree levels (undergraduate, graduate, and doctoral) in social work education. Study results reveal an increase in participant reflective and integrative learning, and an increase in higher-order learning. Qualitative findings support the results through four emergent themes: (1) experience of inquiry-based learning, (2) adjustments required for learning process, (3) impactful facilitators to learning, and (4) developing deep learning. Implications and recommendations are offered for higher education and professional programs.